Procedure to improve the heritage properties management in the historic center of Matanzas, Cuba - Soto-Portillo, Dariel; Sánchez-Suárez, Yasniel; Cabrera-Hernández, Alfredo; Santos-Pérez, Orlando (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
The management of historic centers and heritage properties is a topic that has been widely addressed internationally; however, there are still problems that threaten their efficiency and sustainability. Therefore, the objective of the research is to develop a procedure for the improvement of the management of heritage properties in historic centers. A procedure is designed based on gaps identified in other analyzed procedures, describing its implementation in stages. The results are presented as a general characterization, the integral diagnosis, as well as the proposal for improvements to manage the properties of the historic center, which is broken down into four axes that constitute a compendium of the multiple edges with which the subject is handled. It is concluded that, although there are methodological limitations, key variables are defined within the procedure: heritage value, functional compatibility, state of conservation, sustainability, comfort; which contributes to the generalization of the same and to the management of the institutional framework in charge.